Group A streptococcal sore throat in a periurban population of northern India: a one-year prospective study - Nandi Sobhan; Kumar Rajesh; Ray Pallab; Vohra Harpreet; Ganguly Nirmal K. (The World Health Organization, 2001)
OBJECTIVE: To estimate the incidence and risk factors of group A streptococcus (GAS) sore throat among school-aged children living in a periurban slum area of Chandigarh, North India. METHODS: A total of 536 children aged 5-15 years from 261 families identified by a systematic random selection method were enrolled in the study. Episodes of sore throat were recorded through fortnightly home visits over a one-year period. The local vernacular (Hindi) terms gala kharab (bad throat) and khansi jukam (cough and cold) were used to identify symptoms of sore throat, and throat swab specimens were collected from children who had these symptoms on the day of the home visit. Bacterial culture was carried out and the isolation of GAS was confirmed using group-A-specific antiserum. FINDINGS: The incidences of sore throat and GAS sore throat were, respectively, 7.05 and 0.95 episodes per child-year. The incidence was higher in the following situations: among 11-year-olds, during the winter (November to January) and rainy (August) months (a bimodal peak), among children living in houses where there was no separate room for the kitchen, and in homes that included a tobacco smoker. CONCLUSION: The results show that the incidence of GAS sore throat was related to age, season, and indoor air pollution.